Interaction of Peat Soil and Sulphidic Material Substratum: Role of Peat Layer and Groundwater Level Fluctuations on Phosphorus Concentration - Arifin Fahmi; Bostang Radjagukguk; Benito Heru Purwanto (UNIVERSITY OF LAMPUNG, 2014)
Phosphorus (P) often becomes limiting factor for plants growth. Phosphorus geochemistry in peatland soil is associated with the presence of peat layer and groundwater level fluctuations. The research was conducted to study the role of peat layer and groundwater level fluctuations on P concentration in peatland. The research was conducted on deep, moderate and shallow peat with sulphidic material as substratum, peaty acid sulphate soil, and potential acid sulphate soil. While P concentration was observed in wet season, in transition from wet to dry season, and in dry season. Soil samples were collected by using peat borer according to interlayer and soil horizon. The results showed that peat layer might act as the main source of P in peatland with sulphidic material substratum. The upper peat layer on sulphidic material caused by groundwater level fluctuations had no directly effect on P concentration in the peat layers. Increased of P concentration in the lowest sulphidic layer might relate to redox reaction of iron in the sulphidic layer and precipitation process. Phosphorus concentration in peatland with sulphidic material as substratum was not influenced by peat thickness. However, depletion or disappearance of peat layer decreased P concentration in soil solution. Disappearance of peat layer means loss of a natural source of P for peatland with sulphidic material as substratum, therefore peat layer must be kept in order to maintain of peatlands. [How to Cite: Arifin F, B Radjagukguk and BH Purwanto. 2014. Interaction of Peat Soil and Sulphidic Material Substratum: Role of Peat Layer and Groundwater Level Fluctuations on Phosphorus Concentration. J Trop Soils 19: 171-179. Doi: 10.5400/jts.2014.19.3.171]